2005
DOI: 10.1113/jphysiol.2005.084673
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient deprivation induces sex‐specific changes in thyroid hormone receptor and deiodinase expression in the fetal guinea pig brain

Abstract: Thyroid hormone deprivation during fetal life has been implicated in neurodevelopmental morbidity. In humans, poor growth in utero is also associated with fetal hypothyroxinaemia. In guinea pigs, a short period (48 h) of maternal nutrient deprivation at gestational day (gd) 50 results in fetuses with hypothyroxinaemia and increased brain/body weight ratios. Thyroid hormone action is mediated by nuclear thyroid hormone receptors (TRs) and is dependent upon the prereceptor regulation of supply of triiodothyronin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 62 publications
0
15
1
1
Order By: Relevance
“…In rodents, Dio3 is also expressed in placental tissues and is important in maintaining low thyroid hormone concentrations in the developing fetus (Huang et al, 2003). Up-regulation of Dio3 may lead to lower than normal T3 concentrations in the developing fetus (Chan et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…In rodents, Dio3 is also expressed in placental tissues and is important in maintaining low thyroid hormone concentrations in the developing fetus (Huang et al, 2003). Up-regulation of Dio3 may lead to lower than normal T3 concentrations in the developing fetus (Chan et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…First, Friedhoff et al (2000) found that the effect of artificially restricting maternal thyroid hormone in utero on fetal neurodevelopment and behavioral outcomes was significantly larger in female relative to male rat progeny. Although the mechanism underlying sex-selective effects of maternal nutrient deprivation on brain development could not be directly addressed by their experiment, a recent study of gene expression in nutrient deprived fetal guinea pigs by Chan et al (2005) provides insight into the cellular pathways.…”
Section: B Gender Differences In Iodine Deficiencymentioning
confidence: 99%
“…The effects of ID are more severe in females [24][25][26]41]. The experimental studies conducted by Chan [24] and his colleagues clearly suggest that the female fetus is more sensitive in its cognitive development to maternal ID than is the male. In developing countries, iodine deficiency is seen as an obstacle to women's achievement [42].…”
Section: Data Miningmentioning
confidence: 90%
“…ID is one of the major causes of reproductive failure and mental retardation. Clinical research in ID sensitivity has made it clear that female fetuses are more sensitive than male ones [24][25][26].…”
Section: Research Problemsmentioning
confidence: 99%